Harvest Gypsies in the San Francisco News, Oct. 12, 1936 - San Francisco News:::Publisher:::::::::::: (San Francisco News, 2024)
Page 8 of the San Francisco News, Oct. 12, 1936, with the Harvest Gypsies conclusion article featuring photographs by Dorothea Lange. Steinbeck's name does not appear on this article. It is possible that the Editors wrote this last article of the series.